MEDIUM-TERM RESULTS OF THE USE OF CEMENTLESS, PLASMA-COATED WITH DISPERSED TITANIUM POWDER AND HYDROXYAPATITE, ANATOMICAL ACETABULAR CAGES - Hristo Petrichev; Spas Radev; Valentin Petrov; Petko Ganev; Valeri Stavrev (Journal of IMAB)
Background: The purpose of this study is to report the medium-term clinical and radiographic results of Paprosky type II and III acetabular bone defects revised with a cementless anatomical cage and cemented lipped acetabular cup. Methods: We retrospectively analyzed 58 patients who underwent revision hip arthroplasty with cementless anatomical cages and lipped cemented acetabular cups between April 2009 and December 2013. We registered the following bone defects: Paprosky type IIA - 12 patients, Paprosky type IIB – 15 patients, 14 patients were with Paprosky type IIIA - 14 patients and with Paprosky type IIIB – 17 patients (pelvic discontinuity). Clinical assessment included Harris Hip Score (HHS) and Short Form-12 (SF-12). The radiographic assessment included the center of rotation, cage migration, and osteointegration of the implant. Results: We followed up the patients included in our series with a mean follow-up of 89.5 months (range 38–141), The Harris Hip Score (HHS) improved from 29.5 (12–41) points preoperatively to 87.7 (57–96) points during the last follow-up, and the Short Form – 12 (SF–12) also increased. In 1 patient we did revision due to cage loosening and broken screw 57 months after surgery. In 2 patients we registered non-progressive radiolucency in the AP and Lateral radiographs without any clinical complaints. Conclusion: The cementless anatomical cage combined with a cemented lipped acetabular cup achieves a good result with a high osteointegration rate in Paprosky type II and III acetabular bone defects.